The Coral Triangle Atlas: An Integrated Online Spatial Database System for Improving Coral Reef Management - Cros, Annick; Fatan, Nurulhuda Ahamad; White, Alan; Shwu Jiau Teoh; Tan, Stanley; Handayani, Christian; Huang, Charles; Peterson, Nate; Li, Ruben Venegas; Siry, Hendra Yusran; Fitriana, Ria; Gove, Jamison; et al. (Public Library of Science, 2014)
In this paper we describe the construction of an online GIS database system, hosted by WorldFish, which stores bio-physical, ecological and socio-economic data for the ‘Coral Triangle Area’ in South-east Asia and the Pacific. The database has been built in partnership with all six (Timor-Leste, Malaysia, Indonesia, The Philippines, Solomon Islands and Papua New Guinea) of the Coral Triangle countries, and represents a valuable source of information for natural resource managers at the regional scale. Its utility is demonstrated using biophysical data, data summarising marine habitats, and data describing the extent of marine protected areas in the region.